(untitled) (LACCEI, 2024)
The graduate competencies of students must frequently adapt to the needs of the market so that they can increase the competitiveness of countries. In the case of engineering students, these competencies are changing ever faster. Including Industry 4.0 technologies and innovation in different fields implies a multidisciplinarity in the development of these students. This work has focused on the available literature answering what competencies and methodological strategies are used in the training of engineers. In addition, it has sought to understand the role of the actors of the educational systems and other factors that influence them. In this sense, the competencies related to sustainability, innovation, and industry 4.0 have recently presented an important development in the training of engineers since it allows them to face present and future social, economic, and technological challenges. These paradigms reveal that both teachers and students are immersed in a continuous and changing training system. In turn, it reveals the challenges of current educational systems at the university level and from K-12 in executing the appropriate instruments for developing and evaluating these competencies.